Why shrinkwrap a cucumber? : the complete guide to environmental packaging - Miller, Laurel, ....-; Aldridge, Stephen, ....- (London : Laurence King, 2012)
Designed for all those involved in the packaging industrypackaging designers, manufacturers and retailersthis book provides a comprehensive illustrated guide to designing environmentally friendly packaging. Containing comprehensive directories of different packaging materials, including their environmental credentials, and of different packaging formats, this book offers those seeking to answer design briefs with an environmental requirement a comprehensive guide to the possibilities available to them.
Includes index.
Keywords: Packaging -- Environmental aspects